An intermodal hub location problem for container distribution in Indonesia. (April 2019) - Mokhtar, Hamid; Redi, A.A.N. Perwira; Krishnamoorthy, Mohan; Ernst, Andreas T.
Abstract: In this paper, we extend traditional hub location models for an intermodal network design on a sparse network structure. While traditional hub location problems have been employed for developing network designs for many specific applications, their general assumptions – such as full connectivity, uniform transfer mode, and direct connections between access nodes and hubs – restrict their direct applicability to real-world logistics problems in several ways. In many network design contexts, the usage of versatile transfer modes and hubs is required due to different pricing of modes and topological considerations. In this paper, we extend the traditional hub location problem by incorporating three transfer modes and two kinds of hubs. As an important additional modification, we do not assume that the underlying network is fully connected, or that hubs and access nodes are directly connected. The context for our modelling is intermodal container movements in an archipelago. We develop and formulate an intermodal hub location problem. We show that this problem is NP-hard. Furthermore, a dataset for intermodal hub location problem is provided, based on a real-world container distribution problem in Indonesia. This dataset involves three modes of transport and a sparse network structure. We perform computational experiments and analyse our computational results. Our model provides insights for decision making and determining pricing policies for the desired levels of network flow.